Real‐world volatile organic compound emission rates from seated adults and children for use in indoor air studies. (18th August 2017) - Stönner, C.; Edtbauer, A.; Williams, J.
Abstract: Human beings emit many volatile organic compounds (VOCs) of both endogenous (internally produced) and exogenous (external source) origin. Here we present real‐world emission rates of volatile organic compounds from cinema audiences (50‐230 people) as a function of time in multiple screenings of three films. The cinema location and film selection allowed high‐frequency measurement of human‐emitted VOCs within a room flushed at a known rate so that emissions rates could be calculated for both adults and children. Gas‐phase emission rates are analyzed as a function of time of day, variability during the film, and age of viewer. The average emission rates of CO2, acetone, and isoprene were lower (by a factor of ~1.2‐1.4) for children under twelve compared to adults while for acetaldehyde emission rates were equivalent. Molecules influenced by exogenous sources such as decamethylcyclopentasiloxanes and methanol tended to decrease over the course of day and then rise for late evening screenings. These results represent average emission rates of people under real‐world conditions and can be used in indoor air quality assessments and building design. Averaging over a large number of people generates emission rates that are less susceptible to individual behaviors.